Antioxidant and Antibacterial Properties of Flavonoids in Gyrinops Versteegii Tea Leaves - Parwata, Adi; Kusuma, Angga; Pratama, Bayu; Purwa Hita, Putu Gede Adi (KnE Life Sciences, 2022)
Gyrinops versteegii leaves are high in flavonoids, which have a variety of biological and pharmacological properties. The focus of this research was to determine the antioxidant and antibacterial activity of flavonoids in Gyrinops versteegii leaf water extracts. In this study, extraction was by maceration and partitioning, separation and purification was by chromatography, identification of compounds was carried out using UV-Vis and FTIR spectrophotometers, and antioxidant activity was measured with the DPPH method and antibacterial activity with the diffusion disc method. Flavonoids were thereby isolated. The ethyl acetate extract had the highest total flavonoid content, with 186.976 mg QE/100 g. With inhibition zone diameters of 19 and 13 mm, ethyl acetate extract was the strongest extract in inhibiting the growth of S. aureus and E. coli in the antibacterial activity test. Flavonoids were identified as flavonols after isolation, phytochemical screening, and UV-Visible and FTIR spectroscopic identification. The isolated flavonols had potent antioxidant activity (IC50 = 60.27 ppm) as well as potent antibacterial activity (inhibition zone diameters of 33.82 mm for S. aureus and 23.22 mm for E. coli). The findings therefore showed that tea made from Gyrinops versteegi leaves contains the flavonoid flavonol, which has antibacterial and antioxidant properties. Keywords: Gyrinops versteegii, Flavonol, DPPH, antibacterial and antioxidant